1993
DOI: 10.1007/bf02348607
|View full text |Cite
|
Sign up to set email alerts
|

Botanical and chemical composition of rumen contents of Sika deer on Mt Goyo, northern Japan

Abstract: Botanical and chemical compositions of the rumen contents of 58 Sika deer on Mt Goyo, northern Japan, collected from summer of 1988 to spring of 1989, were analyzed. Sasa nipponica, a dwarf bamboo, was important in summer (35.0%) and winter (61.4%), but it decreased to 5.6% and was replaced by browse leaves in fall, and to 28.0% and was replaced by dead leaves, twigs and bark of woody plants in winter. Crude protein was 20-25 % lower in the washed fraction than in the gross fraction. It was highest (16.2 %) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Their study further suggested that the crude protein content of deer-fed plant species declines in the summer. Fecal and stomach content analyses of sika deer have indicated higher protein concentrations in the summer (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993). These studies suggest that summer is a protein-poor season (Yokoyama et al 2000); however, sika deer need protein-rich food (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Their study further suggested that the crude protein content of deer-fed plant species declines in the summer. Fecal and stomach content analyses of sika deer have indicated higher protein concentrations in the summer (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993). These studies suggest that summer is a protein-poor season (Yokoyama et al 2000); however, sika deer need protein-rich food (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993).…”
Section: Discussionmentioning
confidence: 97%
“…Fecal and stomach content analyses of sika deer have indicated higher protein concentrations in the summer (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993). These studies suggest that summer is a protein-poor season (Yokoyama et al 2000); however, sika deer need protein-rich food (Takatsuki and Ikeda 1993;Watanabe and Takatsuki 1993). In fact, there is evidence indicating that northern cervids accumulate body weight in the summer to prepare for the rutting season (Kaji et al 2006) and the winter (Mitchell et al 1976).…”
Section: Discussionmentioning
confidence: 97%
“…Washed RN has been used as a proxy for DN in previous studies (Klein 1968, Klein and Schrnheyder 1970, Takatsuki and Ikeda 1993, Asada and Ochiai 1999, Latham et al 1999. In addition, nitrogen concentration determined without first washing the rumen contents (unwashed RN) has also been used to approximate DN (Holechek et al 1982, Waid and Warren 1984, Takatsuki and Ikeda 1993, Watanabe and Takatsuki 1993, Soper et al 1993. Because washed RN is strongly correlated with unwashed RN (Takatsuki and Ikeda 1993), we consider that both methods could reflect DN.…”
Section: Diet Compositionmentioning
confidence: 99%
“…Deer in the south of Japan also occur in habitats with a relatively stable food supply, whereas in the north there is considerable seasonal variation in the quality of food. This places dietary stress on animals during winter (Takatsuki and Ikeda 1993;Asada and Ochiai 1999) when unpalatable plants are increasingly browsed (Takahashi and Kaji 2001). Second, exclosure plot studies in the Kaimanawa sika deer range have shown that once deer browse was removed by fencing plots or shooting deer, mountain beech seedling growth and establishment increased after only one year .…”
Section: Without Sika Deermentioning
confidence: 99%